2016
DOI: 10.3892/etm.2016.3994
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits migration of lung cancer cells via the inhibition of matrix metalloproteinases-2 and −9

Abstract: Abstract. Lung cancer is among the most common causes of cancer-related mortality. It has a high mortality rate and resistance to chemotherapy due to its high metastatic potential. Naringenin, a bioactive compound identified in several fruits, displays anti-inflammatory and antitumor effects. Furthermore, naringenin mitigates the migration of several human cancer cell types. However, the effects of naringenin on lung cancer remain unclear. The current study investigated the mechanisms of naringenin on the migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 26 publications
4
47
0
1
Order By: Relevance
“…Desmethylanhydroicaritin from Sophora flavescens exhibited antimigration of U87MG cells by inhibition of MMP‐2 and MMP‐9 activities and protein expression . Naringenin also has been shown to suppress migration via downregulation of MMPs expression in bladder and lung cancer . In line with these observations, treatment with naringenin significantly decreased the activities and expression of MMP‐2 and‐9 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Desmethylanhydroicaritin from Sophora flavescens exhibited antimigration of U87MG cells by inhibition of MMP‐2 and MMP‐9 activities and protein expression . Naringenin also has been shown to suppress migration via downregulation of MMPs expression in bladder and lung cancer . In line with these observations, treatment with naringenin significantly decreased the activities and expression of MMP‐2 and‐9 in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, naringenin blocked TGF‐1/SMAD3 downstream signals, reduced mesenchymal makers' expression, and attenuated MMP‐2 and MMP‐9 activities, and consequently suppressed migration and invasion in pancreatic cancer cells . Recent reports also indicated that naringenin decreased AKT and MMP‐2 activities and inhibited migration in bladder cancer and lung cancer cells …”
Section: Introductionmentioning
confidence: 98%
“…reported the ability of naringenin to modulate the inflammatory responses triggered by Chlamydia trachomatis in mouse macrophages. Chang et al . reported the role of naringenin as an inhibitor of human lung cancer cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…ketchup, juice, sauces, paste, puree) . Furthermore, tomato fruit can be regarded as a functional food because of its content of antioxidant substances, such as ascorbic acid, lycopene and phenols, thus playing a protective role in humans against cancer as well as chronic diseases …”
Section: Introductionmentioning
confidence: 99%
“…prostate and oral cancer (Tu et al, 2016;Han et al, 2018b) Naringenin anti-proliferation CCND1, EREG, ESR2, MAPK1/14 cervical, colon, colorectal cancer, and hepatocarcinoma (Totta et al, 2004;Song et al, 2015;Zhang et al, 2016) Targets Cancer types Ref inhibiting metastasis AKT1, CDH1, MAPK1/4, MMP2/9, NCL, NFKB, PKCZ, PKCE, RAC1, RHO, RHOA, SCN9A, SNAIL1/2, TGFB1, TWIST1, VIM breast, lung, and bladder cancer (Liao et al, 2014;Zhang et al, 2016;Chang et al, 2017;Aktas and Akgun, 2018;Han et al, 2018c;Zhao et al, 2019b) promoting apoptosis AKT1, MAP3K5, ATF3, BAX, BCL2, BIRC5, CASP3/9, JNK, MAPK1/3/14, TP53, RPS6KB1, ROS1, RPS6…”
Section: Discussionmentioning
confidence: 99%